Visual Performance and Perception as a Target of Saccadic Strategies in Patients With Unilateral Vestibular Loss. Issue 6 (November 2018) - Trinidad-Ruiz, Gabriel; Rey-Martinez, Jorge; Batuecas-Caletrio, Angel; Matiño-Soler, Eusebi; Perez-Fernandez, Nicolas
Abstract : Objectives: To evaluate the ability of saccadic strategies developed during vestibular compensation to reduce the effect of an impaired vestibulo-ocular reflex (VOR) on a retinal smear and image motion sensation. Design: Twenty patients with unilateral vestibular loss were examined with a video head impulse test before and after vestibular rehabilitation (VR) with the use of gaze stabilization and refixation saccades training. Head and eye velocity functions were processed to infer the retinal eccentricity, and through its correlation with visual acuity (VA), several measurements are proposed to evaluate the influence of VR on saccades behavior and visual performance. To isolate the effect of saccades on the findings and avoid bias because of gain differences, only patients whose VOR gain values remained unchanged after VR were included. Results: Improved contribution of covert saccades and reduction of overt saccades latency were measured after VR. We found significant differences when assessing both the interval less than 70% VA (50.25 ms), which is considered the limit of a moderate low vision, and less than 50% VA (39.515 ms), which is the limit for severe low vision. Time to recover a VA of 75% (near normal) was reduced in all the patients (median: 56.472 ms). Conclusion: Despite the absence of VOR gain improvement, patients with unilateral vestibular loss are able to develop saccadic strategies that allow the shortening of the interval of retinal smear and image motion. The proposed measurements might be of use to evaluate VR outcomes and visually induced impairment.